Song dynasty figures of longing and desire : gender and interiority in Chinese painting and poetry - Blanchard, Lara C. W. (Women and gender in China studies ;, 2018)
In Song Dynasty Figures of Longing and Desire, Lara Blanchard examines the writing of interiority in paintings of women, considering correspondences to examples of erotic poetry and how such works address the concerns of artists, patrons, and viewers.